2014
DOI: 10.1086/677371
|View full text |Cite
|
Sign up to set email alerts
|

The Robyn Barst Memorial Lecture: Differences between the Fetal, Newborn, and Adult Pulmonary Circulations: Relevance for Age‐Specific Therapies (2013 Grover Conference Series)

Abstract: Pulmonary arterial hypertension (PAH) contributes to poor outcomes in diverse diseases in newborns, infants, and children. Many aspects of pediatric PAH parallel the pathophysiology and disease courses observed in adult patients; however, critical maturational differences exist that contribute to distinct outcomes and therapeutic responses in children. In comparison with adult PAH, disruption of lung vascular growth and development, or angiogenesis, plays an especially prominent role in the pathobiology of ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 155 publications
0
23
0
Order By: Relevance
“…Vascular injury during susceptible periods of lung growth and adaptation can have longstanding effects throughout childhood and may impact distal lung airspace structure as well (6). The most striking examples include the important impact of PVD after premature birth, the contribution of PVD to poor outcomes in many developmental lung diseases, the association of PVD with genetic syndromes (especially Down syndrome), and other factors that reflect both prenatal and postnatal influences that may act through epigenetic mechanisms (7,8). Along with hemodynamic changes during the transition at birth, normal maturation of the lung circulation also plays a critical role during lung organogenesis and formation of the distal airspace through angiocrine signaling, and disruption of endothelial function can impair lung structure in diverse neonatal diseases (9,10).…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Vascular injury during susceptible periods of lung growth and adaptation can have longstanding effects throughout childhood and may impact distal lung airspace structure as well (6). The most striking examples include the important impact of PVD after premature birth, the contribution of PVD to poor outcomes in many developmental lung diseases, the association of PVD with genetic syndromes (especially Down syndrome), and other factors that reflect both prenatal and postnatal influences that may act through epigenetic mechanisms (7,8). Along with hemodynamic changes during the transition at birth, normal maturation of the lung circulation also plays a critical role during lung organogenesis and formation of the distal airspace through angiocrine signaling, and disruption of endothelial function can impair lung structure in diverse neonatal diseases (9,10).…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Likely due to the dysregulation of IGF-1 in the neonatal period, a conditional knockout of IGF-1 in SMCs is protective only in neonatal mice exposed to chronic hypoxia, and not in adult mice. This highlights the complexity of the interactions between normal physiological processes and pathophysiologic stimuli, with particular focus on age (43). In addition to implicating IGF-1 in the development of neonatal PH, we have shown that targeting the IGF-1/IGF-1R pathway using a smallmolecule inhibitor can be a possible therapeutic strategy.…”
Section: Discussionmentioning
confidence: 83%
“…Broncho‐pulmonary anastomoses, as seen on autopsy of Patient 1 (Figure 1e), are known to be present in early life, during which they may increase in number, but eventually obliterate (McMullan, Hanley, Cohen, Portman, & Riemer, ; Robertson, ). However, it is thought that such connections persist in developmental lung disorders as compared to controls of the same age (Abman et al, ). Broncho‐pulmonary anastomoses have been found in the autopsy specimens of children with the previously mentioned pathologies and in adults with severe idiopathic pHTN (Abman et al, ; Acker et al, ; Bush et al, ; Galambos, Sims‐Lucas, & Abman, ; Galambos, Sims‐Lucas, Abman, & Cool, ).…”
Section: Discussionmentioning
confidence: 99%